Activation Policies in Switzerland - Duell, Nicola (OECD Social, Employment and Migration Working Papers, 2010)
This report examines the performance of public employment services and the effectiveness of activation strategies in Switzerland. It covers the role of the key actors in labour market policy, the placement function of the Public Employment Service (PES), the structure of out-of-work benefits and the related incentives and disincentives for taking up work, and discusses the main features of active labour market programmes (ALMPs)...